ANALISIS IMPLEMENTASI MANAJEMEN KESELAMATAN RADIASI SINAR-X DI UNIT KERJA RADIOLOGI RUMAH SAKIT NASIONAL DIPONEGORO SEMARANG TAHUN 2016 - Nabilah Fairusiyyah; Baju Widjasena; Ekawati Ekawati (Jurnal Kesehatan Masyarakat (Undip), 2016)
In medical, Radiation dose which exposed by work activity are higher than another place. Diponegoro National Hospital, which known by national accreditation and classified as a new hospital, is taking an important role on system management for avoiding and reducing radiation hazard. Radiation safety management is important to the workers, due to the characteristic of radiation which not be able to smell and disappeared, so it will be dangerous to safety and health workers.  If the radiation are exposing workers continuously, it will causing disease to mortality on radiation workers. The aim of this study was to analyse implementation X-Ray radiation safety management in Radiology Department, Diponegoro National Hospital. This study used qualitative descriptive research with in-depth interview and observation. The study conducted 6 people as main respondents and 3 people as triangulation respondents. The result showed that radiology installation have 4 doctors with radiology specialists, 1 staff radiation protection, 5 radiographers, but there are no medical physicians and administration staff. In this department, only one staff that already joined training as a staff radiation protection which held by Badan Pengawas Tenaga Nuklir. Health monitoring on workers already conducted in periodic, which every once in a year through working. However, there are no examination before work and also before workers resign. Radiology department already having personal protective equipment, such as apron, radiation screen, Pb gloves, Pb glasses, Tiroid cover, gonad apron. With this variety equipment, radiology department still lacking of the amount in that equipment. In this radiology department, personal radiation dose monitoring used TLD and dose monitoring around workplace just conducted in first use of X-ray device. Radiology department already stored documentation on radioactive substances and X-ray device.